Antimycobacterial activity of some Brazilian indigenous medicinal drinks - D. G. OLIVEIRA; K. A. PRINCE; C. T. HIGUCHI; A. C.B. SANTOS; L. M.X. LOPES; M. J.S. SIM?ES; C. Q.F. LEITE (São Paulo State University (UNESP), 2009)
Tuberculosis (TB) is a very serious problem worldwide and the increasing number of multiple drugs resistant TB cases makes the search for new anti-TB drugs an urgent need. Indigenous knowledge about the use of native plants to treat illnesses has contributed to the discovery of new medicines. In this study, the antimycobacterial activity of seven medicinal drinks was assessed: Ananas sativus (hydroalcoholic fruit extract), Aristolochia triangularis (aqueous and hydroalcoholic leaf, root and stem extracts), Bromelia antiacantha (hydroalcoholic fruit extract), Stryphnodendron adstringens (hydroalcoholic bark extract), Tabebuia ovellanedae (hydroalcoholic bark extract), Vernonia polyanthes (hydroalcoholic root extract), all used by the Vanuíre indigenous community in the treatment of respiratory diseases. The activity was evaluated by using a time-to-kill assay, in which Mycobacterium tuberculosis H37Rv was cultured on Löwenstein-Jensen medium, after thirty minutes, one, three, six, twelve and twenty-four hours contact of the bacteria with each drink. Within half to one hour contact, the hydroalcoholic drinks of A. triangularis, S. adstringens, T. ovellanedae and V. polyanthes reduced the bacterial growth by 2 orders of magnitude in CFU/mL, and all bacterial growth was absent after three hours contact. In contrast, no mycobactericidal effect was detected in the aqueous extract of A. triangularis or in the hydroalcoholic beverages of A. sativus and B. antiacantha, even after twenty-four hours contact. Keywords: Tuberculosis; indigenous drinks; Aristolochia triangularis; Stryphnodendron adstringens; Tabebuia ovellanedae; Vernonia polyanthes.